Assessing the performance of multi-InDel panels for human identification among admixed Brazilians - Ramos, Livia Carla; Kobachuk, Luciellen D G; Nadur, Douglas Mendes; Sabbag, Luiza Rauen; Rosário, Marianna Maia Taulois do; Naslavsky, Michel S; Mendes-Junior, Celso Teixeira; Castelli, Erick da Cruz (Elsevier, 2024)
Insertion/deletion polymorphisms, or InDels, are widely present in the human genome. They have been considered as potential markers for forensic analysis because they can be genotyped using the CE platform and compatible typing techniques used in forensic laboratories. Additionally, InDels have lower mutation rates and often short amplicon sizes, making them ideal for detecting degraded samples. However, most InDels are bi-allelic; therefore, their discrimination power is relatively low. A new set of genetic marker called multi-InDels was reported to improve InDel's informativeness. Multi-InDel markers are generally designated as microhaplotypes encompassing two or more InDels within a short distance, usually less than 200 bp. In this study, we evaluated the applicability of three previously proposed panels of multi-InDel markers, designed for Asian populations, for human identification in Brazil. We assessed all the multi-InDel markers using high-coverage whole-genome sequencing data from a census-based cohort of 1171 Brazilians residing in São Paulo, the largest Brazilian capital. The results showed that most markers are informative for Brazilian individuals since they present more than three frequent haplotypes with different sizes. However, most markers are prone to amplification/sequencing errors due to repetitive or low-complexity regions. Among the tested panels, the one from Huang et al. (2014) is the most promising for forensic use in Brazil, with a combined match probability and cumulative power of exclusion of 4.92 ×10-14 and 0.9991, respectively. Nevertheless, these values are low compared to the ones obtained with CODIS STRs (short tandem repeats) and larger SNP (single nucleotide polymorphisms) panels. Therefore, new attempts to scan the human genome for highly polymorphic multi-InDel markers are still necessary to obtain a suitable panel of multi-InDels for worldwide populations.